Verruciform Xanthoma of the Esophagus: Two Case Reports With Review of the Literature. (May 2020) - Noguchi, Hirotsugu; Kitazono, Ikumi; Hamada, Kazumasa; Tanaka, Takako; Tasaki, Takashi; Shirahama, Hiroshi; Yamamoto, Yoshimasa; Tanimoto, Akihide
Verruciform xanthoma is a rare benign verrucopapillary lesion that develops in the oral mucosa and genital skin. Its development in the esophagus is extremely rare, with only 5 reported cases. We present 2 cases of verruciform xanthoma of the esophagus. Case 1 involved a 91-year-old woman, who had hypertension and chronic gastritis with Helicobacter pylori infection, with a 12-year history of a 10-mm white-yellow elevated lesion on the esophagus, 35 cm from the incisor teeth. Case 2 involved a 70-year-old man with fundic gland polyp, hyperlipidemia, and lung cancer, who had a 10-mm whitish granular/verrucoid lesion on the esophagus, 28 cm from the incisor teeth. Microscopically, these lesions show verrucous and papillomatous epithelial hyperplasia with neutrophilic intraepithelial exocytosis. The histological hallmark is the presence of numerous foamy histiocytes infiltrating the elongated squamous epithelial papillae. Although its etiology is unknown, irritation or trauma caused by radiotherapy has been suggested.